Validity of the Maternal Antenatal Attachment Scale-Spanish Version for Mexican Pregnant Women - Alexa Ferrara-Torres; José R. Álvarez-Carrillo; Mª Asunción Lara; Diana Ibarra-Patrón; Mónica Manjarrez-García; Olga D. Gutiérrez-Hernández; Silvana Mendoza-Ruiz; Daniela Escobedo-Belloc (Clínica y Salud. Investigación Empírica en Psicología, 2023)

(untitled)
During pregnancy, parents experiment emotions, thoughts, and behaviors related to their unborn child as precursors of attachment in the caretaker-infant dyad. The Maternal Antenatal Attachment Scale (MAAS) is an instrument that has shown adequate psychometric properties to evaluate this construct in developed countries. The aim of this study was to assess the reliability and concurrent validity of the Maternal Antenatal Attachment Scale-Spanish version for Mexican women (MAAS-Spanish version). A sample of 142 women in their third trimester of pregnancy who received care in a tertiary hospital was selected. The full scale of the MAAS-Spanish version obtained a Cronbach alpha of .79. A significant negative correlation was found between the global MAAS-Spanish version score (r = -.23, p ≤ .01) and the Postpartum Depression Predictors Inventory-Revised and depressive symptoms (r = -.36 , p ≤ .01). The translated and adapted scale has adequate internal consistency and concurrent validity to measure this construct in this population.